2020
DOI: 10.1111/raq.12497
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and prospects of Viral Envelope protein VP28‐based control strategies to combat white spot syndrome virus in penaeid shrimps: a review

Abstract: VP28 is an essential WSSV envelope protein used to develop innate immune recognition in shrimp against WSSV, owing to its remarkable capability to localize on the surface of shrimp epithelial cells. Transgenically engineered viral VP28 protein from several expression systems was used to increase the survival chances of shrimp against WSSV pathogen, and their efficacy was found to last for 2-3 weeks following therapy. Though few reports have shown that DNA vaccination using the VP28 DNA construct is capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…It was found that these crayfish exhibited enhanced resistance to WSSV 66 . Following this idea, transgenically engineered VP28 proteins from several expression systems were widely used to increase the survival chances of shrimp against WSSV, and their efficacy was found to last for 2–3 weeks following therapy 67 . In addition, immuno‐stimulation with sequence specific dsRNA gave protection against target viral diseases 68 .…”
Section: Disease Control and Preventionmentioning
confidence: 99%
“…It was found that these crayfish exhibited enhanced resistance to WSSV 66 . Following this idea, transgenically engineered VP28 proteins from several expression systems were widely used to increase the survival chances of shrimp against WSSV, and their efficacy was found to last for 2–3 weeks following therapy 67 . In addition, immuno‐stimulation with sequence specific dsRNA gave protection against target viral diseases 68 .…”
Section: Disease Control and Preventionmentioning
confidence: 99%
“…During infection, VP28 serves as a viral binding protein binds to Rab7 protein in shrimp cells and mediates the fusion of virus envelope and host cell membrane, thus helping virus to enter host cells [7] [9], which plays a key role in the early stage of WSSV infection [8]. Therefore, the envelope protein VP28 is an ideal target for screening antiviral drugs [10] In the screening of WSSV antiviral lead compounds, peptide ligands with anti WSSV activity were obtained through phage surface display using VP28 as the target [11] and antibody peptide ligand screening [12] [13] [14]. Especially, Yi et al selected a phage-displayed peptide 2E6 can specifically bound to WSSV, it also had a high specificity and blocked virus infection, with the possible critical motif for virus inhibition being VAVNNSY.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism of WSSV virus entry into shrimp is still unknown, it is speculated that the virus entry into host cells is through the interaction between virus envelope protein and host cell receptor [7]. Since the virus enters the host cell through the interaction between the virus envelope protein and the host cell receptor, it is very important for the discovery of interaction blockers, especially for the development of antiviral drugs [8]. Among all of the known structural proteins of WSSV, VP28 is the main envelope [9] protein, encoded by the reading frame wsv421 [10].…”
Section: Introductionmentioning
confidence: 99%